Alternate Attendance Parades in the Japanese Domain of Satsuma, Seventeenth to Eighteenth Centuries: Pottery, Power and Foreign Spectacle. (December 2022) - Clements, Rebekah
Abstract: This study examines the practice of 'alternate attendance' ( sankin kōtai ), in which the daimyo lords of Tokugawa Japan (1600–1868) marched with their retainers between their home territories and the shogunal capital of Edo, roughly once a year. Research on alternate attendance has focused on the meaning of daimyo processions outside their domains ( han ), along Japan's highways and in the city of Edo. Here I argue that, even as daimyo embarked upon a journey to pay obeisance to the shogun, the ambiguous nature of sovereignty in early modern Japan meant that alternate attendance could also be used for a local agenda, ritually stamping the daimyo's territory with signs of his dominance, much like what has been highlighted in the study of royal processions in world history. I focus on the seventeenth to eighteenth centuries, providing a case study of visits made by the Shimazu family, lords of Satsuma domain, to a village of Korean potters within their territory, whose antecedents had been brought as captives during the Imjin War of 1592–8. During daimyo visits, a relationship of mutual benefit and fealty between the Shimazu and the villagers was articulated through gift-giving, banqueting, dance and displays of local wares. This in turn was used to consolidate Shimazu power in their region.